Examining the practice and role of EGovernment: The case study of president’s office ethics secretariat - Mohamed, Majid Pharis (Mzumbe University, 2024)
Dissertation submitted to the School of Public Administration and Management In partial fulfillment of the requirements for the award of degree of Masters of Science in Human Resource Management of Mzumbe University